In situ injection of phenylboronic acid based low molecular weight gels for efficient chemotherapy. (October 2016) - Gao, Wenxia; Liang, Yan; Peng, Xinyu; Hu, Yalong; Zhang, Longgui; Wu, Huayue; He, Bin
Abstract: Injectable low molecular weight gels (LMWGs) based on the derivatives of phenylboronic acid were prepared and used as substrates for efficient in situ chemotherapy. The gelators as well as LMWGs were characterized by 1 H NMR, UV–vis, FTIR, MS and SEM. Anticancer drug doxorubicin hydrochloride (DOX) was encapsulated in the gels. The rheological properties and rapid recovery capability of both blank and drug-loaded gels were tested. The LMWGs were non-toxic to both 3T3 fibroblasts and 4T1 breast cancer cells. The gels were formed rapidly after injected in vivo. The in vivo anticancer activities of DOX-loaded LMWGs were investigated in breast cancer bearing mice. The intratumoral injection of DOX loaded LMWGs with dose of 30 mg/kg revealed that the gels could coat around the tumor tissues to release DOX sustainingly and maintain effective DOX concentration for chemotherapy. The systemic toxicity of DOX was reduced significantly with the in situ administration of LMWGs formulations. The injectable LMWGs exhibited excellent therapeutic efficacy and low side effects in local chemotherapy.